Perkembangan Lanskap Kesenian Bangkalan Pasca Beroperasinya Jembatan Suramadu - Mutmainnah Mutmainnah; Iqbal Nurul Azhar (DIMENSI - Jurnal Sosiologi, 2022)
The aim of this study is to explain the changes in the cultural landscapes after Suramadu Bridge started operating. The data collection techniques were observation, interviews and documentation on art figures in Bangkalan. The data analysis methods were proposed by Miles and Huberman technique. The result of this studi show that the existence of the Suramadu Bridge does not have a significant impact of the development of arts in Bangkalan. This is marked by not many new arts studios appearing in Bangkalan. The local government’s attention to Bangkalan arts has also not changed. The responses of the people of Bangkalan to the arts has also changed. In the past, art was considered as a luxury. Now, it is still like that but if art has to be paid for, their reception is not good.